THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the transformative role of Artificial Intelligence (AI) in English language teaching (ELT). It explores how AI-powered tools and platforms are reshaping traditional pedagogical approaches by offering personalized learning experiences, real-time feedback, and adaptive instructional content. The article reviews key AI technologies currently used in language education, discusses their benefits and limitations, and highlights the evolving role of teachers in AI-integrated classrooms. Drawing on recent research and practical examples, the study concludes that AI, when thoughtfully implemented, serves as a powerful complement to human instruction, enhancing learner engagement, autonomy, and overall language proficiency.
Keywords: artificial intelligence, English language teaching, personalized learning, natural language processing, adaptive technology, ELT, digital education, language acquisition.